The Effect of Student Worksheet With Creative Problem Solving Based On Students Problem Solving Ability - Ichsan Ichsan; Desty Endrawati Subroto; Ratna Ayu Pawestri Kusuma Dewi; Almira Ulimaz; Ilham Arief (Departement of Mathematics Education, 2023)
The purpose of this research is to ascertain the impact of employing student worksheets based on creative problem solving on students' problem-solving abilities and mastery of concepts. This study was carried out at a high school employing a nonequivalent control group design and a quasi-experimental methodology. Purposive sampling was used to do the sampling. Two classes of senior high school students made up the study's sample, with the control class having 30 individuals. The written test, which included up to 15 essay questions, was used to collect the data. The findings indicated that the use of creative problem-solving student worksheets did not affect problem-solving abilities but did affect mastery of the concept of the circulatory system.